2007
DOI: 10.1631/jzus.2007.b0604
|View full text |Cite
|
Sign up to set email alerts
|

Crossover randomized controlled trial of the electronic version of the Chinese SF-36

Abstract: Objectives: to verify the feasibility and reliability of the electronic version of Chinese SF-36 based on the Quality-of-Life-Recorder. Design: A crossover randomized controlled trial, comparing a paper-based and an electronic version of the Chinese SF-36, was conducted. According to generated random numbers, interviewees were asked to fill out either the electronic version or the paper version first. The second version was filled in after a pause of at least 10 min. Settings and participants: One group of 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 10 publications
2
10
0
Order By: Relevance
“…Approximately four‐fifths of the patients with diabetes in this study preferred to use the cD‐QOL over the pD‐QOL. This is consistent with other studies that found that patients preferred a computerized mode over a paper‐based mode of administration . In addition, most of the patients with diabetes in this study reported that the cD‐QOL was easy to use, even though 43.7% of them had either rarely or never used a PC in their daily life.…”
Section: Discussionsupporting
confidence: 91%
“…Approximately four‐fifths of the patients with diabetes in this study preferred to use the cD‐QOL over the pD‐QOL. This is consistent with other studies that found that patients preferred a computerized mode over a paper‐based mode of administration . In addition, most of the patients with diabetes in this study reported that the cD‐QOL was easy to use, even though 43.7% of them had either rarely or never used a PC in their daily life.…”
Section: Discussionsupporting
confidence: 91%
“…Though the study by Chen et al (2007) had identified the feasibility and reliability of the electronic version of the Chinese SF-36 and its advantages over the paper version, we provided both the electronic and the paper version of the Chinese SF-36 as instruments for assessing HRQOL. When the respondents chose the paper version, the data were first checked and then manually entered into the electronic SF-36 to get scores of subscales automatically.…”
Section: Measurement Toolsmentioning
confidence: 99%
“…Short Form-36 (SF-36) is widely used in medical research as a general health measure [7,8]. Three studies have compared an Internet version of SF-36 with a pen-and-paper version and calculated test-retest reliability [9][10][11]. In these studies the patients filled in the second version of SF-36 within a few hours after the first version.…”
Section: Introductionmentioning
confidence: 99%